Stereospecific Synthesis of γ, δ‐Diamino Esters. Issue 4 (28th November 2013) - Chin, Jik; Kwon, Soon Ho; Kim, Hyunwoo; Chin, Peter; So, Soon Mog; Kim, B. Moon
Abstract: γ, δ‐Diamino acid structural motifs are commonly found in bioactive molecules. We report a one‐pot reaction for the synthesis of γ, δ‐diimino esters with two adjacent chiral centers in enantiomerically pure form through diaza‐Cope rearrangement reaction of diimines formed from ( R, R )‐1, 2‐bis(2‐hydroxyphenyl)‐1, 2‐diaminoethane ( hpen ) and aldehydes. DFT computation provides interesting insights into the stereospecific rearrangement reaction. The crystal structure of a product diimine formed from the reaction of ( R, R )‐ hpen and 2, 6‐dichlorobenzaldehyde shows that the reaction gives the product diimine in S, S configuration. Abstract : Diaza‐Cope rearrangement reactions of diimines formed from 1, 2‐bis(2‐hydroxyphenyl)‐1, 2‐diaminoethane and aldehydes were used to synthesize a variety of γ, δ‐diimino esters followed by hydrolysis of diimines to obtain desired chiral γ, δ‐diamino esters. DFT computation provides interesting insights into the stereospecific rearrangement reaction.